KEEFEKTIFAN PENGGUNAAN MEDIA AUDIOVISUAL TERHADAP PEMBELAJARAN MENULIS TEKS BERITA SISWA SMP NEGERI 1 MAIWA ENREKANG - Sri Husni S; Mayong; Nurhusna (STKIP Subang, 2026)
This study is a quantitative research employing an experimental method with a pre-experimental design, specifically the one-group pretest–posttest design. The objective of this research is to determine the effectiveness of audiovisual media in improving students’ news text writing skills at SMP Negeri 1 Maiwa Enrekang. The research instruments consisted of pre-test and post-test sheets. Data were collected through observation, documentation, and tests. The data analysis techniques included normality testing and hypothesis testing using SPSS version 23. The results showed that the average score of students’ learning outcomes before the use of audiovisual media was 30.86, while after the implementation of audiovisual media the average score increased to 72.90. Based on these findings, it can be concluded that the use of audiovisual media has a significant effect on improving writing skills and learning outcomes of students in class VIII-3 at SMP Negeri 1 Maiwa Enrekang.